Adoption Of Environmental Management Practices (Emps) In The Malaysian Hotel Industry: An Investigation On Emps Drivers And Market Performance Outcomes - Kamalulariffin, Noor Shairullizan (2013)
This study seeks to investigate the extent of the adoption of Environmental Management Practices (EMPs) among four- AND five- star hotels in Malaysia. This study also attempts to identify if regulation/government, customer demand, level of competition, greenness at the organisational level, and attitude of organisational level towards change act as the key drivers of EMPs. In addition, this study aims to determine if market performance acts as the outcome of EMPs. The comprehensiveness of environmental management system (EMS) and management stakeholder relations represent EMPs, whereas market performance is measured through three dimensions i.e. the effectiveness, efficiency, and adaptability measure of market performance. The population of this study is four- and five- star hotels in Malaysia. This study applied institutional theory to support this framework. Respondents consisted of one hundred and two (102) out of two hundred and three (203) mailed questionnaires and the survey method was employed for purpose of data collection. The results of the study showed that four- and five- star hotels in Malaysia implement the EMPs to a moderate extent. In general, cultural-cognitive isomorphism which is greenness at the organisational level acts as the main driver for hotels to implement EMPs. In addition, the study found that market performance is the outcome of EMPs. Besides to protect the environment, hotels can also ensure the sustainability of their business by incorporating environmentally friendly practices and improving their market performance.